Low Dose of X‐Ray‐Excited Long‐Lasting Luminescent Concave Nanocubes in Highly Passive Targeting Deep‐Seated Hepatic Tumors - Chen, Zheng‐Zhe; Wang, Liu‐Chun; Manoharan, Divinah; Lee, Chin‐Lai; Wu, Lai‐Chin; Huang, Wan‐Ting; Huang, Eng‐Yen; Su, Chia‐Hao; Sheu, Hwo‐Shuenn; Yeh, Chen‐Sheng (Advanced materials (Weinheim), 2019)
Chromium‐doped zinc gallate, ZnGa2O4:Cr3+ (ZGC), is viewed as a long‐lasting luminescence (LLL) phosphor that can avoid tissue autofluorescence interference for in vivo imaging detection. ZGC is a cubic spinel structure, a typical agglomerative or clustered morphology lacking a defined cubic shape, but a sphere‐like feature is commonly obtained for the nanometric ZGC. The substantial challenge remains achieving a well‐defined cubic feature in nanoscale. The process by which dispersed and well‐defined concave cubic ZGC is obtained is described, exhibiting much stronger LLL in UV and X‐ray excitation for the dispersed cubic ZGC compared with the agglomerative form that cannot be excited using X‐rays with a low dose of 0.5 Gy. The cubic ZGC reveals a specific accumulation in liver and 0.5 Gy used at the end of X‐ray excitation is sufficient for imaging of deep‐seated hepatic tumors. The ZGC nanocubes show highly passive targeting of orthotopic hepatic tumors. Dispersed and well‐defined ZnGa2O4:Cr3+ (ZGC) concave nanocubes are reported as providing highly passive targeting of deep‐seated hepatic tumors. They also exhibit much stronger long‐lasting luminescence in UV and X‐ray excitation for the dispersed cubic ZGC compared with the agglomerative form that cannot be charged using X‐rays with a low dose of 0.5 Gy.